Characterization of infrastructure and geology of natural attractions in the region of Santo Antônio do Rio Abaixo/MG as a subsidy for the development of ecotourism in sustainable bases (Research, Society and Development, 2018)
Tourism is considered to be one of the main economic activities in the world because it allows the emergence of businesses to meet the needs of tourists, on the other hand, this activity can trigger negative impacts on the environment in the absence of adequate planning and organization. In this context, the municipality of Santo Antônio do Rio Abaixo (MG) is known for its natural attractions, such as Poço do Limão, Praia do Tabuleiro and Balneário Benedito Martins Leite, which attract tourists to the town. Thus, this work aimed to characterize the infrastructure for tourism service and the local geology of seven tourist attractions, located in this municipality, identifying the potential of these for the development of tourist modalities. It was noted that, in general, natural resources have the potential to develop different tourism modalities, such as ecotourism, adventure tourism and geotourism, however, the absence of signs is an aspect that needs to be adequate. In relation to the local geology, it was verified that gneiss rocks correlated to the Dona Rita and Gouveia complexes. It should be noted that the geology of the region should be observed not only for tourism planning, but also for the use and occupation of the soil of the region, given the natural susceptibility to soil erosion from gneiss rocks, avoiding the degradation of these areas.